Structural Design and Assessing of Recombinantly Expressed African Swine Fever Virus p72 Trimer in Saccharomyces cerevisiae - Meng, Kaiwen; Zhang, Yueping; Liu, Qi; Huyan, Yangnan; Zhu, Wenzhuang; Xiang, Ye; Meng, Geng (Frontiers in Microbiology, 2022)
In an effort to control the outbreak of the African Swine Fever Virus (ASFV), there is an urgent need to develop an effective method to prevent the pandemic, including vaccines and diagnostic methods. The major capsid protein of ASFV p72 (B646L), which forms a trimer with each monomer adopting a double jelly roll fold, is the main component of the virus particle and major antigen of ASFV. Thus, the p72 protein may be considered an antigen candidate for vaccine and diagnostic development. However, the development of ASFV p72 trimer for the industry application, including veterinary usage, faces unavoidable challenges: firstly, the low cost of the antigen production is required in vaccine and diagnostic application; and, secondly, whether produced antigen folds in its native conformation. Here, based on the information provided by the atomic structure of p72, we have successfully performed rational mutagenesis on p72 trimers and expressed it in Saccharomyces cerevisiae with high yields. The cryo-EM structure of recombinant expressed p72 trimer is determined at 4.18 Å in resolution. The correlation coefficient between this structure and the ASFV virus structure is 0.77, suggesting a highly similar fold of this trimer with the native protein on the virus particle.